Analysis of the Behavior of Forgiveness as a Believer's Responsibility - Djone Georges Nicolas; Wajar Budiman Laia; Suyanto; Oktavian Harefa; Anjur Pasaribu (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to analyze the behavior of believers towards the act of forgiveness as a responsibility before God, using a descriptive qualitative method approach, and collecting data through various books including the Bible, interviews, journals, digital media, and documents related to topic of study in this research. Forgiveness is one of the most effective actions to solve problems in a believer's life. However, it is suspected that there are many among believers who have not been able to apply it to others, thus causing problems with the growth of faith in God. Then the result, forgiveness becomes the right and right action that must be done by believers according to God's commands.